Study on Sensitive Mechanism of Micro Jet Angular Velocity Sensor Based on Fluid-solid Coupling - Wang, Yuxin; Piao, Linhua; Li, Bei (2019 IEEE 4th Advanced Information Technology, Electronic and Automation Control Conference (IAEAC), 2019)
Fluid-solid coupling analysis is carried out for the sensitive mechanism of micro-jet angular velocity sensor. The fluid-structure coupling method based on ANSYS and CFX is used to calculate the distribution of gas velocity at different input angular velocities at the thermal resistance wire in the angular velocity sensor. The results show that the gas velocity at the two symmetrical thermistor wires is equal at rest; the deviation of gas velocity is proportional to the angular velocity in the range of 0°/s to 60°/s; and the difference of gas velocity at the two symmetrical thermistor wires increases with the increase of angular velocity. Fluid-solid coupling analysis opens up an effective way for optimum design of micro jet angular velocity sensor.